Mechanisms of Resistance Against Cancer Therapeutic Drugs - Chatterjee, Shailja; G. Damle, Satyawan; K. Sharma, Anil (Current Pharmaceutical Biotechnology, 2014)
Cancer is the manifestation of multiple dysregulated cellular pathways. Treatment protocols engaged in treating these diseases involve mainly the cell cycle regulating genes/proteins, DNA synthesis and repair, protein synthetic machinery, apoptotic and proliferation activity and cytoskeletal framework. Some of the traditional therapeutic strategies have over the years developed resistance making cure difficult to achieve. This paper analyzes the mechanisms employed by various cancers that render them resistant against therapeutic drugs.
Keywords: radiation